Geometry effects on the electronic properties of multi-open dots structures - Fagotto, EAM; Rossi, S. M.; Moschim, E. (Ieee-inst Electrical Electronics Engineers Inc, 1998)
In this paper we show that the electronic properties of multi-open dots structures are strongly modified by even smalt changes in their geometries. Our discussion of these effects is done in terms of the interaction among localized states (dot-like) and extended states (channel-like), from which a Fano resonance situation arises.
Keywords: quantum dots; quantum effect semiconductor devices; quantum wires; resonant tunneling devices